Vaccine hesitancy in the era of COVID-19: could lessons from the past help in divining the future? - Wiysonge, Charles Shey; Ndwandwe, Duduzile; Ryan, Jill; Jaca, Anelisa; Batouré, Oumarou; Anya, Blanche-Philomene Melanga; Cooper, Sara (Human vaccines & immunotherapeutics, 2022)
Vaccine hesitancy, which embodies the unwillingness to receive vaccines when vaccination services are available and accessible, is one of the greatest threats to global health. Although vaccine hesitancy has existed among a small percentage of people for centuries, its harmful effects are likely to be more pronounced during the COVID-19 pandemic than ever before. COVID-19 vaccine hesitancy will pose substantial risks for both people who delay or refuse to be vaccinated and the wider community. It will make communities unable to reach thresholds of coverage necessary for herd immunity against COVID-19, thus unnecessarily perpetuating the pandemic and resulting in untold suffering and deaths. Vaccine hesitancy is pervasive, misinformed, contagious, and is not limited to COVID-19 vaccination. Our work shows that vaccine hesitancy is a complex and dynamic social process that reflects multiple webs of influence, meaning, and logic. People's vaccination views and practices usually comprise an ongoing engagement that is contingent on unfolding personal and social circumstances, which can potentially change over time. Therefore, as COVID-19 vaccination rolls out globally, scientists and decision-makers need to investigate the scale and determinants of vaccine hesitancy in each setting; so that tailored and targeted strategies can be developed to address it.